Yersinia enterocolitica Bacteremia Associated with a Ruptured Abdominal Aortic Aneurysm: A Case Report with Literature Review - Yordan Kalchev; Hristina Urdzhanova; Stefan Stanev; Bogomila Cheshmedzhieva; Maria Pavlova; Gergana Lengerova; Marianna Murdjeva (Microorganisms, 2023)
Yersinia enterocolitica is a foodborne pathogen, mainly associated with disorders involving the gastrointestinal tract, including diarrhea, ileitis, and mesenteric lymphadenitis. Extraintestinal presentation is uncommon in healthy individuals, but bacteremia is reported in immunocompromised hosts. We present a 74-year-old male with Y. enterocolitica serogroup O:3 bacteremia who complicated to rupture of an abdominal aortic aneurysm. With the current case report, we aimed to emphasize the association of Y. enterocolitica bacteremia with abdominal aortic aneurysm rupture. Better surveillance is needed, not only to reduce morbidity and mortality but also to update current epidemiological data on the incidence of such associations.